Ambivalent Stereotypes and Persuasion: Attitudinal Effects of Warmth vs. Competence Ascribed to Message Sources - Linne, Roman; Schäfer, Melanie; Bohner, Gerd (Frontiers in Psychology, 2022)
The stereotype content model (Fiske et al., 2002) defines warmth and competence as basic dimensions of social judgment, with warmth often dominating perceptions; it also states that many group-related stereotypes are ambivalent, featuring high levels on one dimension and low levels on the other. Persuasion theories feature both direct and indirect source effects (Bohner et al., 1995). Joining both approaches, we studied the persuasiveness of ambivalently stereotyped sources. Participants (total N = 296) read persuasive arguments attributed to groups stereotyped as either low in competence but high in warmth (e.g., housewives) or vice versa (e.g., lawyers). In Study 1, high competence/low warmth sources were more persuasive than low competence/high warmth sources. In Study 2, this pattern replicated when an accuracy motive had been induced, whereas it reversed when a connectedness motive had been induced. These source effects were direct, that is, independent of message processing. We discuss our findings in terms of the persuasiveness of warmth versus competence of the source as being dependent upon recipient motivation; we also consider theoretical implications and perspectives for future research.